Sexual Health After Different Modes of Delivery, Implications for Patient Education - A Narrative Review - Fengier, Maria; Grzelak, Oliwia; Trzaskowski, Jakub; Kącikowska, Justyna; Sordyl, Katarzyna; Rogulski, Krzysztof; Kuśmierczyk, Weronika; Majkowska, Magdalena; Bolek, Oliwia; Szczepański, Piotr (Journal of Education, Health and Sport, 2026)
Background. Female sexual dysfunction is a common problem among women in the postpartum period. Changes in sexual satisfaction are often attributed to hormonal changes, perinatal trauma, anxiety and relational problems. In recent years, increasing attention has been paid to instrumental obstetric interventions during delivery, the mode of birth, and their potential impact on women’s sexual function. Postpartum sexual health is often neglected and disregarded as an unimportant part of human life. Although many women fear its decline in the postpartum, the impact of the mode of delivery on sexual health remains insufficiently addressed in educational programs. Aim. The aim of this narrative review was to investigate the relationship between the mode of delivery and postpartum sexual function. Materials and methods. A total of 18 studies were selected to analyze the possible correlation between the mode of delivery and sexual function. Various instruments assessing sexual function were used, including the FSFI, self-report questionnaires, SQOL, SHOW-Q. The primary database used for the literature search was PubMed for studies published between 2009 and 2025. Additionally, reference lists of relevant articles were screened. Results. The majority of studies included in this review demonstrated no long-term difference in overall sexual function between vaginal delivery and cesarean section. Some studies, however, reported transient sexual dysfunction in the early postpartum period. Conclusions. The analysis demonstrated that the mode of delivery has no long-term effect on women’s sexual function, although some studies reported transient dysfunction in the early postpartum period. Counseling and education of pregnant women are important in addressing concerns about postpartum sexual dysfunction.